Whole-genome analysis of Lysinibacillus boronitolerans MSR1: A dairy-isolated multidrug-resistant and non-pathogenic strain - Md. Shahedur Rahman; Md. Tofidul Islam; Mahadi Hasan; Md. Tariquzzaman; Nure Sharaf Nower Samia; Md. Mahfuzur Rahman; Mustafizur Rahman (PLoS ONE, 2025)
Lysinibacillus boronitolerans MSR1, a bacterium isolated from yogurt, was characterized through a detailed genomic and phylogenetic analysis. The strain demonstrated the ability to grow in MRS broth at pH 5–8 and exhibited positive activity in citrate utilization, catalase, oxidase, Methyl Red–Voges Proskauer (MR-VP), and Triple Sugar Iron (TSI) tests while being negative for amylase degradation and sulfide production. Whole-genome sequencing and Average Nucleotide Identity (ANI) analysis revealed a close genetic relationship between MSR1 and previously reported L. boronitolerans strains, with ANI values ranging from 95.25% to 98.30%, particularly for L. boronitolerans strain NBRC103108. Phylogenetic analyses based on whole-genome and 16S rRNA sequences confirmed the taxonomic placement of MSR1 within the L. boronitolerans species. A circular genome comparison highlighted the presence of unique genomic regions in MSR1, notably around the 3500 kbp mark, indicating the acquisition of novel genes that may contribute to its distinct phenotypic traits. Antibiotic susceptibility testing revealed a high level of resistance in MSR1 to glycopeptides and aminoglycosides, while the strain remained susceptible to imipenem, with in silico analysis identifying key antimicrobial resistance (AMR) genes, including qacJ , vanW , vanT , and FosBx1 , which confer resistance to disinfectants, vancomycin, and fosfomycin through efflux pumps and target modification mechanisms. Five distinct biosynthetic gene cluster (BGC) regions were identified in the MSR1 genome, encoding genes for lanthipeptide-class-iii, RiPP-like, T3PKS, beta-lactone, terpene, and NRPS-like clusters. Pan-genome analysis suggested that L. boronitolerans possesses an open pan-genome, with a substantial proportion of accessory and unique genes. Functional annotation of core, accessory, and unique genes revealed that core genes are predominantly associated with metabolic processes, while accessory and unique genes are involved in information processing, storage, and defence mechanisms. These findings enhance our understanding of the genomic diversity, evolutionary dynamics, and potential adaptive strategies of L. boronitolerans MSR1, providing new insights into its ecological and functional roles.